A Campus Climate/Violence Survey's Psychometrics and Findings. (November 2021) - Follingstad, Diane R.; Chahal, Jaspreet K.; Bush, Heather M.; Coker, Ann L.; Li, Caihong R.; Wu, Xian; Brancato, Candace; Carlson, Charles R.
Data from a campus climate/violence survey (CCS) include psychometric information for survey items/scales plus findings from a large state university to promote its usefulness for assessment of interpersonal violence/harassment. This CCS can thus be evaluated for its measurement and documented findings, allowing for benchmarking purposes. An innovative measurement strategy is introduced to comprehensively capture incidence of victimization types through streamlined questioning. Tables provide detailed data for 6, 995 undergraduate and graduate/professional students over a 1-year period. Adding to published literature on existing CCSs, this article provides the range of information needed for universities to determine the potential usefulness of a CCS.